2017
DOI: 10.1111/neup.12436
|View full text |Cite
|
Sign up to set email alerts
|

Giant intracranial arteriovenous malformation as the focus of epileptic seizures

Abstract: A man in his late thirties was found in a supine position in the hallway of his house. He had been diagnosed with epilepsy at approximately 20 years old. Since stopping treatment, epileptic events occurred more frequently and his condition deteriorated in the past 2 years. Autopsy revealed that head injuries were found on the left side of his head. A fracture from the left parietal bone to the anterior cranial fossa was also detected. A subdural hemorrhage (hematoma) spanned a wide range. A subarachnoid hemorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Therefore, autopsy sometimes reveals rare lesions. We previously reported on some peculiar lesions, such as rare arteriovenous malformations, in this journal …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, autopsy sometimes reveals rare lesions. We previously reported on some peculiar lesions, such as rare arteriovenous malformations, in this journal …”
Section: Introductionmentioning
confidence: 94%
“…We previously reported on some peculiar lesions, such as rare arteriovenous malformations, in this journal. 2,3 In this report, we describe a case of an interhemispheric cyst with a partial defect of the corpus callosum in an elderly man.…”
Section: Introductionmentioning
confidence: 96%
“…However, information on the risk of caffeine exposure has only been uncovered using forensic autopsies. Takayama et al reported the case of a male in his early 20's working a night shift, whose cause of death was diagnosed as caffeine intoxication 9 . He consumed many energy drinks to stay awake and alert, but this resulted in excessive caffeine intake.…”
Section: Toxicological Analysismentioning
confidence: 99%
“…3 Su etiología es variada e incluye el accidente cerebrovascular, 4-8 la enfermedad de Alzheimer, 9-13 el traumatismo craneoencefálico, [14][15][16] infecciones (abscesos, meningitis, encefalitis y VIH), [17][18][19] malformaciones cerebrales congénitas, 20,21 lesión cerebral durante el nacimiento, 22 trastornos metabólicos presentes al nacer (fenilcetonuria), 22-24 enfermedades autoinmunes, 22,25 tumor cerebral 26,27 y vasos sanguíneos anormales en el cerebro. [28][29][30][31] La epilepsia es definida por la Organización Mundial de la Salud (OMS) como "la presentación recurrente de fenómenos paroxísticos del sistema nervioso central secundarios a la descarga eléctrica anormal de las neuronas en el cerebro de forma crónica". 3 La Liga Internacional contra la Epilepsia (ILAE por sus siglas en inglés: International League Against Epilepsy) propone la siguiente definición: "es la ocurrencia transitoria de signos y/o síntomas debidos a una actividad neuronal anormalmente excesiva o sincrónica en el cerebro", 32 esto conlleva consecuencias neurobiológicas, sociales, psicológicas y cognitivas.…”
Section: Introductionunclassified